In Vitro and In Vivo Equivalence Testing of Nanoparticulate Intravenous Formulations - Pathak, S. M.; Ruby, P. K.; Aggarwal, D. (Drug Research, 2014)
The topic of bioequivalence evaluation of nanoparticulate intravenous formulations is one that has been intensely debated in recent times since the release of the specific recommendations by many regulatory authorities worldwide. Product specific bioequivalence guidelines for many of the nanoparticulate systems where therapeutic molecules are directly coupled (human albumin bound paclitaxel nanosuspension), functionalized (iron- carbohydrate preparations) or entrapped/coated to a carrier (doxorubicin liposomal formulations), have been approved by the drug regulatory agencies. These current regulatory procedures include complete characterization of the generic formulation in terms of its physicochemical characteristics, pharmacokinetics disposition and/or non clinical testing with respect to the reference formulation. The concept of in vitro equivalency is emerging as a valuable tool in these guidances as generic product differing in in vitro parameters can result in a different biopharmaceutical profile with respect to pharmacokinetics and biodistribution. Furthermore, in case of systems with entrapped drug, classical pharmacokinetic parameters alone may only ensure the equivalent clearance of test and reference product from systemic circulation but may fail to detect the extent to which the nanoparticles are taken up by different target organs and, consequently, the safety and efficacy effects. Hence, additional tissue distribution study in preclinical study models has reflected in recent guidances. Understanding and interpretation of these regulatory requirements thus presents most critical component of a generic product development cycle. This article reviews these current regulatory procedures with special emphasis on in vitro population bioequivalence (POP BE) and preclinical testing of generic formulations.
Keywords: population bioequivalence; intravenous; non clinical; liposomes; in vitro